Effectiveness and cost-effectiveness of The Daily Mile on childhood weight outcomes and wellbeing: a cluster randomised controlled trial - Breheny, Katie (Int J Obes (Lond), 2020)
BACKGROUND: The Daily Mile is designed to increase physical activity levels with children running or walking around school grounds for 15-min daily. It has been adopted by schools worldwide and endorsed as a solution to tackle obesity, despite no robust evidence of its benefits. We conducted a cluster randomised controlled trial to determine its clinical and cost-effectiveness. METHODS: Forty schools were randomly assigned (1:1) to either the Daily Mile intervention or control group in which only the usual school health and wellbeing activities were implemented. The primary outcome was BMI z-score (BMIz) at 12 months follow-up from baseline, with planned subgroup analysis to examine differential effects. Primary economic analysis outcome was incremental cost per Quality-Adjusted-Life-Year (QALY) gained. RESULTS: Using a constrained randomisation approach, balanced on school size, baseline BMIz and proportion of pupils eligible for free school meals, 20 schools were allocated to intervention (n = 1,153 participants) and 20 to control (n = 1,127); 3 schools withdrew (2 intervention, 1 control). At 12 months, BMIz data were available for 18 intervention schools (n = 850) and 19 control schools (n = 820 participants). Using intention-to-treat analysis the adjusted mean difference (MD) in BMIz (intervention − control) was −0.036 (95% CI: −0.085 to 0.013, p = 0.146). Pre-specified subgroup analysis showed a significant interaction with sex (p = 0.001) suggesting a moderate size benefit of The Daily Mile in girls (MD −0.097, 95% CI −0.156 to −0.037). This was consistent with the exploratory economic results that showed The Daily Mile to be highly cost-effective in girls (£2,492 per QALY), but not in boys, and overall to have a 76% chance of cost-effectiveness for the whole sample, at the commonly applied UK threshold of £20,000 per QALY. CONCLUSIONS: Overall the Daily Mile had a small but non-significant effect on BMIz, however, it had a greater effect in girls suggesting that it might be considered as a cost-effective component of a system-wide approach to childhood obesity prevention.